Knowledge and attitude on the nutrition of hospitalised elderly patients among nurses in Hospital Universiti Sains Malaysia - Azhar, Nurulhuda (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia., 2021)
Most developed countries have determined that people aged 65 years and above are considered elderly. As the increasing of elderly patients, high knowledge and positive attitude were crucial to all nurses because they play an essential role in providing holistic care to the elderly during hospitalisation. A cross-sectional study was carried out to study the knowledge and attitude on the nutritional of hospitalized elderly patients among nurses in Hospital USM. The questionnaire used in this study was staff nurses' knowledge and attitude on the nutrition of hospitalised elderly patient’s questionnaire adapted from study by Boaz et al. (2013). A total of 232 nurses in Hospital USM who fulfilled the inclusion and exclusion criteria were selected randomly. Data collected were statistically analysed using the SPSS software version 26.0. Pearson’s Correlation dan Pearson’s Chi- Square were used for data analysis. As for the knowledge and attitude score, the results show 33 (14.2%) for good knowledge and 230 (99.1%) for positive attitude respectively. There was an association between knowledge score and attitude score (p = 0.180), the results show only 19 (8.2%) for respondents who have good knowledge and positive attitude. Lastly, there is no association between age and working experience with the level of knowledge on nutrition (p = 0.929) and (p= 0.184) respectively. In conclusion, nurses' knowledge has to be enhanced and improved so that they are more knowledgeable and competent in providing nutritional care to hospitalized elderly patient.